Tracking Bioluminescent ETEC during In vivo BALB/c Mouse Colonization - Rodea, Gerardo E.; Montiel-Infante, Francisco X.; Cruz-Córdova, Ariadnna; Saldaña-Ahuactzi, Zeus; Ochoa, Sara A.; Espinosa-Mazariego, Karina; Hernández-Castro, Rigoberto; Xicohtencatl-Cortes, Juan (Frontiers in Cellular and Infection Microbiology, 2017)
Enterotoxigenic Escherichia coli (ETEC) is a leading cause of diarrhea worldwide. Adhesion to the human intestinal tract is crucial for colonization. ETEC adhesive structures have been extensively studied; however, colonization dynamics remain uncharacterized. The aim of this study was to track bioluminescent ETEC during in vivo infection. The promoter region of dnaK was fused with the luc gene, resulting in the pRMkluc vector. E. coli K-12 and ETEC FMU073332 strains were electroporated with pRMkluc. E. coli K-12 pRMkluc was bioluminescent; in contrast, the E. coli K-12 control strain did not emit bioluminescence. The highest light emission was measured at 1.9 OD600 (9 h) and quantified over time. The signal was detected starting at time 0 and up to 12 h. Streptomycin-treated BALB/c mice were orogastrically inoculated with either ETEC FMU073332 pRMkluc or E. coli K-12 pRMkluc (control), and bacterial colonization was determined by measuring bacterial shedding in the feces. ETEC FMU073332 pRMkluc shedding started and stopped after application of the control strain, indicating that mouse intestinal colonization by ETEC FMU073332 pRMkluc lasted longer than colonization by the control. The bioluminescence signal of ETEC FMU073332 pRMkluc was captured starting at the time of inoculation until 12 h after inoculation. The bioluminescent signal emitted by ETEC FMU073332 pRMkluc in the proximal mouse ileum was located, and the control signal was identified in the cecum. The detection of maximal light emission and bioluminescence duration allowed us to follow ETEC during in vivo infection. ETEC showed an enhanced colonization and tropism in the mouse intestine compared with those in the control strain. Here, we report the first study of ETEC colonization in the mouse intestine accompanied by in vivo imaging.